Theoretical and Practical Significance of the Physical Education and Sport - ugli, Jurayev Erkin Voitjon; Hudoyberdiyevich, Ortikov Umidjon; Olimjonovich, Murodov Nozimjon (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses the role of physical education and sports in shaping the students' moral and ethical image. The impact of physical education and sport on the human spirit, spirituality and morality is analyzed.